PENERAPAN TEKNOLOGI FUSION FILLING BOTTLE UNTUK MENINGKATKAN EFISIENSI SISTEM AIR CONVEYOR - I Ketut Rai Wijaya; I Ketut Sukaya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
Technology continues to advance with various innovations aimed at simplifying human activities, especially in the industrial sector. To meet industrial demands, tools are needed that can control and operate machine processes automatically, thereby improving labor efficiency. This research focuses on the application of automatic bottle filling technology to enhance the efficiency of the air conveyor system. The research findings reveal that the filling machine for SPS products consists of two rooms and two machines, requiring a long and branching air conveyor to transport empty bottles from the blowing machine to the two filling rooms. This system requires 13 blowers with a capacity of 2.2 kW to ensure the supply of empty bottles. This innovation enables automatic liquid filling into bottles using a microcontroller as the main control system. The automatic filling process showed an average difference in liquid volume between two bottles of 1.3 ml, with a filling speed of two 100 ml bottles in 6.9 seconds. The success rate reached 100%, with an average production rate of 10 bottles per minute and a filling system time of 13 seconds across 100 trials. This indicates that the system can operate in real-time, with data transmission being faster than the production process.